Pre-natal Attachment and Parent-To-Infant Attachment: A Systematic Review - Trombetta, Tommaso; Giordano, Maura; Santoniccolo, Fabrizio; Vismara, Laura; Della Vedova, Anna Maria; Rollè, Luca (Frontiers in Psychology, 2021)
During the perinatal period, the establishment of the attachment relationship with the fetus and subsequently with the real child is crucial for the parents’ and the child’s wellbeing. Coherently with the assumption that the attachment relationship starts to develop during pregnancy, this systematic review aims to analyze and systematize studies focused on the association between prenatal attachment and parent-to-infant attachment, in order to clarify the emerging results and provide useful information for clinical purposes. Nineteen studies were included. Sixteen research identified a positive relationship between prenatal attachment and parent-to-infant attachment, and three articles highlighted a negative association between antenatal attachment and postpartum bonding disorders. These results were found both in women and men, in normative and at-risk pregnancies, adopting different assessment approaches (i.e. self-report measures, observations, and projective measures). However, only small or moderate associations were found Future studies are needed to further confirm these findings across different populations (e.g. male samples, non-normative samples or samples in disadvantaged conditions) and with different methodological approaches (e.g. self-reports and observational measures). Moreover, studies would be needed in order to clarify mechanisms through which prenatal attachment influences parent-to-infant attachment, as well as protective and risk factors which intervene between these two variables.